Growth performance of Wader Cakul juvenile (Puntius binotatus) with different stocking density - Dony Prasetyo; Anis Zubaidah; Vera Noviana (IJOTA (Indonesian Journal of Tropical Aquatic), 2019)
One of the freshwater fishes thatbegan to bedeveloped is Wader fish, but there is still a lot of information that has notbeen supportedon fish farming techniques. One of them is the optimal stocking density for cultivation. The purpose of this study was to study the effects of different stocking densities on the growth and survival rates of the WaderCakulfish (Puntiusbinotatus).This research was conductedin May - July 2018. The method used in this study was to use aCompletely Randomized Design with 4 training, namely P1 (2 fish/liter), P2 (3 fish/liter), P3 (4 fish/liter) and P4 (5 fish/liter).Each treatment was repeated3 times. The main parameters were absolute growth rate (length and weight gain)(GR), specific growth rate (SGR), survival rate (SR), and feed conversion ratio (FCR).Data were analyzedusing ANOVA (analysis of variance) and continued with the Least Significant Difference Test. The results showed that different stocking densities gave significant values (P <0.05) for GR, SGR, SR and FCR comparisons. The best treatment in this study was P1 with a growth value of 0.31 ± 0.01 gram, SGR 3.50 ± 0.03%, Long Growth 1.97 ± 0.05 cm, SR 85.07 ± 2.17% and FCR 1.47 ± 0.02. P1 (2 fish/liter) is the best maintenance to increase the growth, survival rate, and feed efficiency of thecakulwader fish.